A influência da Teoria da Dependência nas Ciências Sociais: Fernando Henrique Cardoso e Ruy Mauro Marini - Santos, Inês Cristina dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this study was to demonstrate the influence of dependency theory in the social sciences, especially after 1964, particularly theses Cardoso and Ruy Mauro Marini that, in different ways, presented the problems inherent to the Brazilian dependent capitalism, each pointing various categories as a way of thinking to overcome or at least a solution to the problems created by this particular form of subordination. Besides presenting the main ideas of the authors , the various analyzes that researchers from various fields of knowledge were also exposed - from the alternatives that Cardoso and Marini proposed for the solution of the Brazilian dependency - discussed, evaluated and commented on draft contributions authors to understand the economic and political problems of the Brazilian inferiority. From the assumption that was the thesis that Cardoso had more influence in the Social Sciences proposing an associated -dependent Brazilian development, the reasons for the predominance of this thinking can be hampered the debate about dependency theory were exposed, making for years, there was the release of a kind of single thought, accepted as unquestionable, which made Marini’s theses being misunderstood or at least staying in the background. From this, the researchers and commentators, these works have gained great importance in this research, since it showed the reasons why there would have been, in Brazil, a debate about authors dependent Marxists - Ruy Mauro Marini, Theotônio dos Santos and Vania Bambirra - exposing the historical reasons for this non-debate. Moreover, the criticism of Fernando Henrique Cardoso and José Serra to Ruy Mauro Marini, as well as the defense of the latter, which until 2000 had not been published in Brazil were exposed. Thus, with the exposition of ideas of Cardoso and Marini was understood that the predominance of the theses of the first studies on...

O objetivo deste trabalho foi demonstrar a influência da teoria da dependência nas Ciências Sociais, especialmente no pós 1964, particularmente as teses de Fernando Henrique Cardoso e Ruy Mauro Marini que, de maneiras distintas, apresentaram os problemas inerentes ao capitalismo dependente brasileiro, cada qual apontando categorias diversas, como forma de se pensar a superação ou no mínimo uma solução para os problemas advindos dessa forma específica de subordinação. Além de apresentar as ideias principais dos autores, também foram expostas as diversas análises que pesquisadores, das mais diversas áreas do conhecimento – a partir das alternativas que Cardoso e Marini propuseram para a solução da dependência brasileira – discutiram, avaliaram e opinaram sobre as contribuições dos autores para a compreensão dos problemas econômico-políticos da subalternidade brasileira. A partir da hipótese de que foi a tese de Cardoso que mais teve influência nas Ciências Sociais propondo um desenvolvimento brasileiro associado-dependente, foram expostos os motivos pelos quais, a possível predominância desse pensamento obstaculizou o debate acerca da teoria da dependência, fazendo com que, durante anos, houvesse a divulgação de uma espécie de “pensamento único”, aceito como inquestionável, e que fez com que as teses de Marini fossem mal compreendidas ou no mínimo ficassem em segundo plano. A partir disso, os pesquisadores e comentadores dessas obras passaram a ter grande importância nesta pesquisa, posto que apresentaram as razões pelas quais não teria havido, no Brasil, um debate acerca dos autores dependentistas marxistas – Ruy Mauro Marini, Theotônio dos Santos e Vânia Bambirra – expondo as razões históricas do “não-debate”. Além disso, foram expostas as críticas de Fernando Henrique Cardoso e José Serra a Ruy Mauro Marini, bem como a defesa do último, que até o ano 2000 não havia sido publicada...
Keywords: Cardoso, Fernando Henrique 1931; Marini, Ruy Mauro, 1932-1997; Desenvolvimento e subdesenvolvimento; Relações econômicas internacionais; Ciências sociais; International economic relations